Case study: drilling rig inoperability due to loud noise complaint - Cano Arratea, Hermes Jilmer (2023)
The case study describes an industrial hygiene investigation initiated in response to a drilling rig down due to complaints of loud noise, workers decide to shut down one of three drilling rigs (P3: Drill 3) due to loud noise. It begins with the requirement of situational investigation of exposure to noise of the drilling workers in order to identify and evaluate the exposure to noise, for this the industrial hygienist performs a series of noise dosimetry detection, which aims to declare the results as acceptable or unacceptable based on current regulations, identify the characteristics of the noise sources under study and propose control measures in accordance with the fundamentals, communicate the fundamentals and controls to the workers and management. The study population is made up of drilling rig operators exposed to noise, population is 10 and the sample is 11, the methodology used for the selection of the sample is NIOSH 77-173. The results were analyzed under the UCL, obtaining as results an acceptable noise exposure profile and below the Maximum Permissible Limit. And it is obtained that, of the three drillers coded as P1: Driller 1, P2: Driller 2 and P3: Driller 3, the latter (paralyzed Driller) is the noisiest among the evaluating teams, however it does not generate a quantitative subdivision of the Group. of Similar Exposure (GES).